Frequency of Appendicular Perforation in Acute Appendicitis Patients (Medical Forum Monthly, 2022)
Objective: To find out the frequency of appendicular perforation among patients with acute appendicitis.Study Design: Descriptive cross-sectional studyPlace and Duration of Study: This study was conducted at the Surgical Department of MTI, Lady Reading Hospital from 1st August 2020 to 31st January 2021.Materials and Methods: This study was designed to determine the frequency of appendicular perforation in acute appendicitis patients. A total of 91 patients of both genders admitted and scheduled for appendectomy were enrolled.Results: The mean age of study participants was 32.6±9.3 years. In our study 55 (60.4%) patients were male and 36 (39.6%) patients were female. 59 (64.8%) patients were admitted from emergency unit while 32 (35.2%) patients were admitted via OPD. During surgery, perforated appendix was recorded in 24 (26.4%) patients.Conclusion: The frequency of appendiceal perforation is relatively high in our population who are subjected to appendectomy. It was found significantly higher in older age groups (p value <0.001), although perforation was seen more often in male patients but association with gender was insignificant (p value 0.810).